Impact of the COVID-19 pandemic on the mental health of transgender persons in India: Findings from an exploratory qualitative study - Raghuram, Harikeerthan; Parakh, Sana; Chidambaranathan, Supraja; Tugnawat, Deepak; Pillai, Venu; Singh, Sanjana; Singh, Satendra; Shaikh, Aqsa; Bhan, Anant (Frontiers in Global Women's Health, 2023)
Introduction: Transgender persons in India who are one of the most vulnerable groups were particularly impacted by the COVID19 pandemic. Increased risk of COVID19, challenges with continuing livelihood, uncertainty, and anxiety around the pandemic over pre-existing social discrimination and exclusion pose risk of a mental health impact as well. To investigate this further, this component of a larger study, on experiences in healthcare of transgender persons in India during COVID19, looks into the question ‘How did the COVID19 pandemic impact the mental health of transgender persons in India’. Methods: 22 In-depth interviews (IDI) and 6 focus group discussions (FGD) were conducted virtually and in-person with persons self-identifying as transgender or belonging to ethnocultural transgender communities from different parts of India. Community based participatory research approach was used by ensuring representation from the community in the research team and through a series of consultative workshops. Purposive sampling with snowballing was used. The IDIs and FGDs were recorded, transcribed verbatim and analyzed using an inductive thematic analysis. Results: Mental health of transgender persons were affected in the following ways. Firstly, COVID19, its associated fear and suffering combined with pre-existing inaccessibility of healthcare and reduced access to mental health care affected their mental health. Secondly, unique social support needs of transgender persons were disrupted by pandemic linked restrictions. Thirdly, pre-existing vulnerabilities such as precarious employment and underlying stigma were exacerbated. Finally, gender dysphoria was a key mediating factor in the impact of COVID19 on mental health with a negative and positive impact. Conclusions: The study reiterates the need to make systemic changes to make mental healthcare and general healthcare services trans-inclusive while also recognizing the essential nature of gender affirmative services and the need to continue them even during emergencies and disaster situations. While this brings out how public health emergencies can exacerbate vulnerabilities, it also shows how the lived mental health experience of transgender person is intricately linked to the way work, travel and housing is structured in our society and therefore points to the structural nature of the linkage between mental health and gender.